The Relationship Between Competitiveness and Social Progress Indicators (International Journal of Scientific Research and Management (IJSRM), 2022)
This research aims to evaluate the existence of empirical evidence on the relationship between the competitiveness index and the social progress index of the countries considered in the sample in the year 2019. To this end, we use indicators that seek to portray in detail their methodologies found in the “Report Social Progress Index”, published in 2019 and in “The Global Competitiveness Report”. The investigated population refers to all countries included in the WEF (World Economic Forum) ranking and those countries included in the IPS (Social Progress Index) ranking in 2019, making a total of 151 and 133 countries, respectively. The sample used refers to 133 countries that had complete data in both databases. The analysis methods used were Exploratory Factor Analysis and the Root Cause function. Empirical results suggest that social convergence reflects the way in which economic performance produces asymmetries in the income distribution of the researched nations, guaranteeing access to certain goods and services considered relevant to the quality of life in order to ensure security functions. facing certain risks. It was found that this work is in line with the findings developed by (Arruda et al., 2009), with regard to the relationship between the competitiveness index and the Gross Domestic Product (GDP) and its main contribution is to be able to provide subsidies to public policy makers when considering competitiveness indicators as beacons for improving the quality of life and social progress of the analyzed nations.